2018
DOI: 10.1002/ar.23917
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Deformation During the Cardiac Mechanical Cycle

Abstract: Cardiomyocytes both cause and experience continual cyclic deformation. The exact effects of this deformation on the properties of intracellular organelles are not well characterized, although they are likely to be relevant for cardiomyocyte responses to active and passive changes in their mechanical environment. In the present study we provide three‐dimensional ultrastructural evidence for mechanically induced mitochondrial deformation in rabbit ventricular cardiomyocytes over a range of sarcomere lengths repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…In recent years, mitochondrial dynamics, such as fusion and fission, has become popular subjects and are involved in the maintenance of mitochondrial health [70,71]. Previous research found that mitochondria elongated their length after cyclic stretching in cardiac cells [72]. Mitochondrial dynamics were also reported as mechano-sensors, which tend to undergo fusion in response to stretching forces in smooth muscle cells [73].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, mitochondrial dynamics, such as fusion and fission, has become popular subjects and are involved in the maintenance of mitochondrial health [70,71]. Previous research found that mitochondria elongated their length after cyclic stretching in cardiac cells [72]. Mitochondrial dynamics were also reported as mechano-sensors, which tend to undergo fusion in response to stretching forces in smooth muscle cells [73].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a link has been demonstrated between mitochondrial activity, cardiac preload modulation via Frank–Starling mechanisms, microtubules, and mitochondria X-ROS production ( 39 , 42 ); however, further investigation is necessary to characterize the underlying mechanism. Subsarcolemmal mitochondria (and possibly interfibrillar mitochondria) deform during sarcomere contraction, and it is possible to appreciate a diastolic and a ‘systolic dimension’ of the organelles ( 49 , 50 ). Importantly, mitochondria can move within the cytoplasm, trafficking among cells in neurons ( 51 ) and also fuse with adjacent mitochondria or split in two parts by fission mechanisms ( Fig.…”
Section: Mitochondrial Calcium Handling Mechanisms: Microtubules-depementioning
confidence: 99%
“…modification of membrane curvature/tension [20,21]; ii) re-distribution of transmembrane proteins [22,23]; iii) modulation of ionic fluxes through mechanosensitive ion channels [24][25][26][27]; iv) deformation of cyto-nucleoskeletal elements [28,29]; and v) reorganization of intracellular organelles [30][31][32].…”
Section: Introductionmentioning
confidence: 99%